Pole piece prepared by ectopic polymerization, preparation method of pole piece, diaphragm-free battery and solid-state battery

The electrode sheet is prepared through ectopic polymerization technology to form an interface flexible layer, which solves the problem of thermal runaway in lithium-ion batteries under extreme conditions and improves the cycle stability and safety performance of the batteries.

CN119920848AActive Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411372948.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-05-02
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to thermal runaway under extreme conditions, resulting in combustion or explosion, and there are uneven polymerization and many side reactions during the electrode recombination process, affecting the battery's circulation and safety performance.

Method used

The electrode sheet is prepared by ectopic polymerization technology, and the prepolymerization precursor liquid is obtained through the first polymerization, and the second polymerization is performed on one side of the current collector to form an interface flexible layer, simplifying the production process and improving production efficiency.

Benefits of technology

It improves the cycle stability of the battery, first-time Coulomb efficiency and safety performance, reduces the interface impedance, enhances the stability of the pole plate structure, and reduces the risk of thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920848A_ABST
    Figure CN119920848A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and discloses a pole piece prepared by ectopic polymerization, a preparation method of the pole piece, a diaphragm-free battery and a solid-state battery. The method for preparing the pole piece by ectopic polymerization comprises the following steps: mixing a monomer and an initiator, and carrying out primary polymerization to obtain a pre-polymerized precursor solution; and introducing the pre-polymerized precursor solution into at least one side of the current collector, and carrying out secondary polymerization so as to form an interface flexible layer on at least one side of the current collector. According to the pole piece prepared by the method provided by the invention, the cycling stability, the first coulombic efficiency and the safety performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a pole piece prepared by heterogeneous polymerization and a preparation method thereof, a solid-state battery, and a diaphragm-free battery. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic products, electric vehicles, energy storage and other fields due to their high energy density and excellent rate performance. At the same time, these devices have increasingly higher requirements for the service life, high temperature performance, energy density and safety performance of lithium-ion batteries. As the operating voltage and energy density of the battery increase, the thermal stability of the battery electrode sheet deteriorates, and thermal runaway is likely to occur under extreme conditions, which brings the risk of battery combustion or even explosion.

[0003] Currently in lithium-ion batteries, solid polymer electrolytes have good processability and flexibility, which can provide good interface contact between the pole piece and the solid electrolyte. However, during the pole piece composite process, the polymerization process cannot be controlled and there are many side reactions, resulting in uniform polymerization, which will increase the interface impedance and further affect the battery's cycle performance, first coulomb efficiency and safety performance. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one object of the present invention is to provide a pole piece prepared by heterogeneous polymerization and a preparation method thereof, a diaphragm-free battery, and a solid-state battery. The pole piece prepared by the method provided by the present application can improve the cycle stability, first coulomb efficiency and safety performance of the battery.

[0005] In the first aspect of the present invention, a method for preparing a pole piece by ex situ polymerization is proposed. According to an embodiment of the present invention, the method comprises: mixing a monomer and an initiator, performing a first polymerization, and obtaining a prepolymer precursor solution; introducing the prepolymer precursor solution into at least one side of a current collector, and performing a second polymerization to form an interfacial flexible layer on one side of the current collector.

[0006] According to the method of the above embodiment of the present invention, the heterotopic polymerization technology is used, and the controllable heterotopic polymerization process of the monomer can be achieved through the first polymerization reaction, ensuring the stable polymerization reaction, improving the consistency of product quality, and further adopting the pole piece composite and interface softening technology, the pole piece of the all-solid-state battery can be constructed in one step, simplifying the production process and improving production efficiency. Compared with the traditional multi-step preparation method, this one-step construction method reduces the errors and losses that may be caused by the intermediate links, and ensures the quality and performance stability of the pole piece. This one-step construction method can make the prepolymer precursor liquid achieve high dispersion and uniform distribution inside and on the surface of the pole piece at the same time. Inside the pole piece, the uniform distribution of the prepolymer precursor liquid can improve the structural stability and ion transmission performance of the active substance. On the surface, the uniformly distributed prepolymer precursor liquid can improve the contact with the solid electrolyte, reduce the interface impedance, promote ion transmission, and construct an ion / electron transmission path. The ion transmission path ensures the rapid migration of lithium ions between the pole piece and the solid electrolyte, and improves the charge and discharge efficiency and rate performance of the battery. The electron transmission path ensures the efficient transmission of electrons in the internal and external circuits of the pole piece, reduces the internal resistance of the battery, and improves the energy conversion efficiency.

[0007] Further, the interface softening of the interface flexible layer can improve the problem of poor solid-solid contact, reduce the interface impedance, thereby improving the ion transmission efficiency, and can also alleviate the interface stress caused by the volume change during the battery charging and discharging process, enhance the stability of the pole piece structure, and thus improve the cycle stability of the battery. In addition, since the active material in the pole piece will release oxygen when working under high voltage, the interface softening can also inhibit the release of oxygen, thereby improving the thermal stability and safety of the battery. Under the action of the initiator, the monomer undergoes a polymerization reaction, and a uniform polymer matrix can be formed in the interface flexible layer. Through the method of ectopic polymerization, during the pole piece composite process, a high-flux ion transmission channel can be constructed, a high dispersion effect of the monomer can be achieved, a uniform polymer matrix can be formed, and a uniform distribution can be achieved in the pole piece, thereby enhancing the stability of the pole piece structure and greatly improving the safety of the battery. The interface flexible layer covers the pole piece, so that the specific surface area of ​​the active material layer is reduced, so that the SEI film formed during the first charge and discharge is smoother, and the side reaction is reduced to effectively improve the first coulomb efficiency of the battery. Therefore, the pole piece prepared by the method provided by the present application can improve the cycle stability, first coulomb efficiency and safety performance of the battery.

[0008] In addition, the method according to the above embodiment of the present invention may also have the following additional technical features:

[0009] In some embodiments of the present invention, before the step of mixing the monomer and the initiator and performing the first polymerization to obtain the prepolymer precursor solution, the method further includes: preparing an active material layer on at least one side of the current collector. Thus, the cycle stability, first coulombic efficiency and safety performance of the battery can be improved.

[0010] In some embodiments of the present invention, after the step of mixing the monomer and the initiator, performing the first polymerization, and obtaining the prepolymer precursor solution, the step of introducing the prepolymer precursor solution to at least one side of the current collector, and performing the second polymerization to form an interfacial flexible layer on one side of the current collector, further comprises: mixing the prepolymer precursor solution with an active material. Thus, the cycle stability, the first coulombic efficiency, and the safety performance of the battery can be improved.

[0011] In some embodiments of the present invention, the active material includes one of a positive electrode active material and a negative electrode active material, thereby facilitating the improvement of the first coulombic efficiency, cycle stability and safety performance of the battery.

[0012] In some embodiments of the present invention, the positive electrode active material includes at least one of nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium vanadium phosphate and lithium-rich manganese-based material.

[0013] In some embodiments of the present invention, the negative electrode active material includes at least one of graphite, graphene, soft carbon, hard carbon, elemental silicon, silicon-oxygen materials, silicon-carbon materials, silicon-nitrogen composite materials, silicon-based alloys, elemental tin, tin oxides, tin-based alloys, lithium metal, lithium alloys, lithium titanium oxides, transition metal oxides and transition metal sulfides.

[0014] In some embodiments of the present invention, the polymerization degree of the prepolymer precursor liquid is 5%-60%. Thus, the prepolymer can maintain a certain fluidity, ensure that the prepolymer precursor liquid can smoothly enter the interior of the pole piece, and solidify in the pole piece, reduce the defects and pores inside the pole piece, prevent the occurrence of micro short circuits, prevent the direct contact between the positive and negative electrodes, thereby preventing the occurrence of large-area short circuits, and improving the safety performance and cycle stability of the battery.

[0015] In some embodiments of the present invention, the viscosity of the prepolymer precursor solution is η, and η satisfies: 0<η≤1000Pa·s. As a result, the prepolymer precursor solution has good fluidity and permeability, so that after the prepolymer precursor solution is introduced into the surface of the pole piece, it can more easily enter the inside of the pole piece and fully fill the pores and structures inside the pole piece, thereby enhancing the stability and integrity of the pole piece, which is conducive to improving the safety performance and cycle stability of the battery.

[0016] In some embodiments of the present invention, the step of mixing the monomer and the initiator and performing a first polymerization to obtain a prepolymer precursor solution includes: mixing the monomer, lithium salt, inorganic filler, conductive agent, cross-linking agent, initiator and solvent, and performing a first polymerization to obtain a prepolymer precursor solution. Thus, the first coulombic efficiency, cycle performance and safety performance of the battery can be improved.

[0017] In some embodiments of the present invention, based on the total mass of the monomer, the initiator, the lithium salt, the inorganic filler, the conductive agent and the cross-linking agent, the mass proportion of the monomer is 0.5%-30%. Thus, an effective polymerization reaction can be carried out under the action of the initiator, which helps to ensure the controllability of the polymerization process, and further optimizes the performance of the interface flexible layer, so that it can better play the role of improving poor solid-solid contact, preventing micro short circuits and large-area short circuits, thereby improving the cycle stability and safety performance of the solid-state battery.

[0018] In some embodiments of the present invention, the monomer includes at least one of acrylate monomers, olefin nitrile monomers, cycloolefin monomers, vinylidene ester monomers, amide monomers, alkyl sulfides, sulfate monomers, borate monomers, cyanamide monomers and quaternary ammonium salt monomers.

[0019] In some embodiments of the present invention, based on the total mass of the monomer, the initiator, the lithium salt, the inorganic filler, the conductive agent and the cross-linking agent, the mass ratio of the lithium salt is 0.5%-30%. Thus, the smooth ion conduction can be ensured, the ion conductivity can be improved, and thus the charge and discharge performance of the battery can be improved, and the electrochemical stability window of the battery can be improved simultaneously, so that the battery can operate within a more stable voltage range during the charge and discharge process, reduce the occurrence of side reactions, and improve the cycle life and safety of the battery.

[0020] In some embodiments of the present invention, based on the total mass of the monomer, the initiator, the lithium salt, the inorganic filler, the conductive agent and the cross-linking agent, the inorganic filler accounts for 5% to 50% by mass, thereby helping to disperse and conduct heat, reduce local overheating, thereby reducing the risk of thermal runaway and improving the safety and cycle performance of the battery.

[0021] In some embodiments of the present invention, the mass of the initiator accounts for 0.1%-3% of the mass of the monomer. Thus, it works well with other components such as monomers, lithium salts, inorganic fillers, conductive agents and cross-linking agents to jointly construct a stable polymer matrix structure, which helps to optimize the performance of the polymer matrix, improve the comprehensive performance of the pole piece, and further improve the cycle stability and safety performance of the battery.

[0022] In some embodiments of the present invention, the D50 particle size of the conductive agent is 5nm-1000nm, preferably 10nm-500nm. As a result, the conductive agent has better dispersibility and can be more evenly distributed in the polymer matrix formed by polymerization of monomers. The uniform distribution can ensure the uniform conduction of current in the pole piece, avoid hot spots and performance degradation caused by excessive local current, and improve the cycle stability of the battery.

[0023] In some embodiments of the present invention, the D50 particle size of the inorganic filler is 2nm-500nm, preferably 10nm-300nm. Thus, it can be more evenly dispersed in the polymer matrix, can better interact with the polymer matrix and other components, improve interface performance, reduce interface impedance, increase interface flatness, promote the transmission of ions and electrons, and improve the electrochemical performance of the battery.

[0024] In some embodiments of the present invention, the inorganic filler includes at least one of an inorganic active filler and an inorganic inert filler.

[0025] In some embodiments of the present invention, the inorganic active filler includes at least one of an oxide active filler, a sulfide active filler, a halide active filler, a nitride active filler, a boride active filler and a hydride active filler.

[0026] In some embodiments of the present invention, the inorganic inert filler includes at least one of an oxide inert filler, a nitride inert filler, a boride inert filler, a halide inert filler, a dielectric ceramic inert filler, a ferroelectric ceramic inert filler, a piezoelectric ceramic inert filler, a diatomaceous earth inert filler, a mullite inert filler, a montmorillonite inert filler and a kaolin inert filler.

[0027] In some embodiments of the present invention, the first polymerization method includes at least one of thermal polymerization, photopolymerization and ultrasonic polymerization.

[0028] In some embodiments of the present invention, the first polymerization method includes heating ultrasonic polymerization combined with thermal polymerization and ultrasonic polymerization. Thus, the safety performance, cycle performance and first coulombic efficiency of the battery can be improved.

[0029] In some embodiments of the present invention, the temperature of the heated ultrasonic polymerization is 30° C.-100° C., preferably 40° C.-60° C. Thus, the energy required for the reaction can be provided, making it easier for the molecules in the reaction system to collide and react, thereby improving the rate and efficiency of the polymerization reaction.

[0030] In some embodiments of the present invention, the frequency of the heating ultrasonic polymerization is 0.5 MHz-5.0 MHz, thereby improving the safety performance, cycle performance and first coulombic efficiency of the battery.

[0031] In some embodiments of the present invention, the heating ultrasonic polymerization time is 1h-12h. Thus, the performance uniformity of the polymer matrix is ​​improved, and good dispersion can reduce the interface impedance, improve the interface flatness, promote the effective transmission of lithium ions in the ceramic phase, ceramic-polymer interface and intervention path, improve the ionic conductivity and electrochemical stability window, and help improve the charge and discharge performance, cycle life and safety of the battery.

[0032] In some embodiments of the present invention, the temperature of the second polymerization is 40° C.-120° C. Thus, sufficient energy can be provided for the second polymerization, the polymerization reaction of the monomer can be accelerated, the degree of the second polymerization can be controlled, the prepolymer precursor liquid and the active material can be better combined, a stable active material layer and an interface flexible layer can be formed, the shedding and deformation of the active material during the charge and discharge process can be reduced, and the cycle life and safety of the battery can be improved.

[0033] In some embodiments of the present invention, the second polymerization time is 10s-2min. Thus, the degree of the second polymerization can be accurately controlled, which helps to form a uniform and stable active material layer and an interface flexible layer, can reduce the shedding and deformation of the active material during the charge and discharge process, and improve the cycle life and safety of the battery.

[0034] In some embodiments of the present invention, the introducing method includes at least one of coating, spraying and dipping.

[0035] In some embodiments of the present invention, the introduction method includes coating, and the coating includes gravure coating. Thus, the thickness and uniformity of the coating can be accurately controlled to achieve a uniform coating effect, ensuring the distribution consistency of the active material and the prepolymer precursor solution on the current collector.

[0036] In some embodiments of the present invention, the gravure coating speed is 0.5 m / min-10 m / min. Thus, the consistency and reliability of the battery can be improved, the problems caused by local performance differences can be reduced, and the safety performance and cycle stability of the battery can be improved.

[0037] In some embodiments of the present invention, the gravure coating has a tension of 30 N to 200 N. Thus, the adhesion between the current collector and the coating can be increased, and the tension makes the current collector in close contact with the gravure roller, which helps the coating to better adhere to the current collector and improve the reliability and cycle stability of the battery.

[0038] In some embodiments of the present invention, the coating thickness of the gravure coating is 0.5 μm-3 μm. Thus, the loading amount of the active material can be ensured while maintaining the stability of the pole piece structure, and the mechanical strength and ion transmission performance of the pole piece can be balanced to a certain extent, thereby extending the cycle life of the battery.

[0039] In some embodiments of the present invention, the method further comprises preparing a solid electrolyte layer on the interface flexible layer. Thus, the rapid migration of lithium ions between the positive and negative electrodes can be promoted, and the charge and discharge performance of the battery can be improved. Compared with traditional liquid electrolytes, solid electrolytes can reduce the risk of leakage and improve the safety of the battery.

[0040] In the second aspect of the present invention, the present invention provides a pole piece prepared by heterogeneous polymerization. According to an embodiment of the present invention, the pole piece prepared by heterogeneous polymerization includes one prepared by the method of the first aspect. The pole piece prepared by heterogeneous polymerization can improve the cycle stability, first coulombic efficiency and safety performance of the battery.

[0041] In the third aspect of the present invention, the present invention provides a diaphragm-free battery. According to an embodiment of the present invention, the diaphragm-free battery includes a pole piece prepared by the method of the first aspect or prepared by the ex situ polymerization of the second aspect. The diaphragm-free battery has excellent safety performance, cycle performance and first coulombic efficiency.

[0042] In a fourth aspect of the present invention, the present invention provides a solid-state battery. According to an embodiment of the present invention, the solid-state battery is prepared by the method of the first aspect or includes a pole piece prepared by the heterogeneous polymerization of the second aspect. The solid-state battery has excellent safety performance, cycle performance and first coulombic efficiency.

[0043] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0045] Figure 1 A schematic diagram of the battery structure obtained by preparing a pole piece using ex situ polymerization according to an embodiment of the present invention is shown.

[0046] Figure Number:

[0047] A pole piece 10, a current collector 1, an active material layer 2, an interface flexible layer 3, and a solid electrolyte layer 4 prepared by heterogeneous polymerization. DETAILED DESCRIPTION

[0048] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0049] In a first aspect, the present invention provides a method for preparing a pole piece by heterogeneous polymerization. According to an embodiment of the present application, the method comprises:

[0050] S1. Mix the monomer and the initiator, perform the first polymerization, and obtain a prepolymer precursor solution.

[0051] In this step, a prepolymer precursor solution can be obtained by mixing the monomer and the initiator and then performing a first polymerization.

[0052] It should be noted that heterotopic polymerization refers to a method in which a prepolymer precursor solution is obtained by first performing a first polymerization, and then the prepolymer precursor solution is introduced into a current collector for a second polymerization to form a pole piece. By using heterotopic polymerization technology, the first polymerization reaction can realize a controllable monomer heterotopic polymerization process, ensure that the polymerization reaction is carried out stably, and improve the consistency of product quality. Further, the pole piece composite and interface softening technology are adopted, and the all-solid-state battery pole piece can be constructed in one step, simplifying the production process and improving production efficiency. Thus, the application of the pole piece preparation technology of the present invention in lithium batteries improves the penetration of the microporous structure of the battery core and the uniformity of the macroscopic distribution of the polymer inside the battery, and solves the problems of uneven polymerization and uneven wetting during in-situ curing. The battery prepared by this method has high ionic conductivity and electrochemical stability window, high mechanical strength and stable cycle performance and excellent safety performance. And the method has low cost, high efficiency, can effectively control the consistency of the product, and has a stable yield, which is conducive to large-scale production and development.

[0053] According to some embodiments of the present invention, the degree of polymerization of the prepolymer precursor liquid is 5%-60%. For example, it can be 5%, 10%, 20%, 40%, 60%, etc. By limiting the degree of polymerization of the prepolymer precursor liquid within the above range, the prepolymer can maintain a certain fluidity, and can ensure that the prepolymer precursor liquid can smoothly enter the pole piece (active material layer) and solidify in the pole piece, thereby reducing the defects and pores inside the pole piece, preventing the occurrence of micro short circuits, and preventing the direct contact between the positive and negative electrodes, thereby preventing the occurrence of large-area short circuits, and improving the safety performance and cycle stability of the battery.

[0054] It should be noted that the degree of polymerization of the prepolymer precursor solution specifically indicates the relative relationship between the actual molecular weight of the polymer and the theoretically achievable limit molecular weight of the polymer in the prepolymer precursor solution. It is presented in percentage form so that we can intuitively understand the growth degree of the polymer and the degree to which it approaches its maximum size.

[0055] According to some embodiments of the present invention, the viscosity of the prepolymer precursor is η, and η satisfies: 0<η≤1000Pa·s. For example, it can be 1Pa·s, 10Pa·s, 100Pa·s, 500Pa·s, 1000Pa·s, etc. By limiting the viscosity of the polymer precursor within the above range, the prepolymer precursor has good fluidity and permeability, so that the prepolymer precursor can more easily enter the interior of the pole piece after being introduced into the surface of the pole piece, thereby enhancing the stability and integrity of the pole piece; and the prepolymer precursor has a certain viscosity, which can ensure that the internal components maintain a high dispersion effect for a long time, and are evenly dispersed when coated on the pole piece, reducing the specific surface area of ​​the pole piece, forming a flat SEI or CEI, which is beneficial to improving the safety performance, coulomb efficiency and cycle stability of the battery.

[0056] There is no special limitation on the method of the first polymerization. For example, the method of the first polymerization includes but is not limited to at least one of thermal polymerization, photopolymerization and ultrasonic polymerization. Those skilled in the art can flexibly select according to needs.

[0057] According to a specific embodiment of the present invention, the first polymerization method includes a heating ultrasonic polymerization combined with thermal polymerization and ultrasonic polymerization. Among them, thermal polymerization can provide energy to promote the polymerization reaction of the monomer; ultrasonic polymerization can enhance the collision and reaction activity of molecules through the cavitation and mechanical effect of ultrasonic waves, thereby improving the polymerization efficiency. In addition, ultrasonic polymerization can also enable monomers, inorganic fillers, etc. to achieve high dispersion distribution in the solution, thereby promoting the uniform distribution of ectopic polymerization of materials, helping to reduce the inhomogeneity of polymerization products, and improving the consistency and stability of materials. The presence of uniformly distributed polymerization and inorganic materials can improve the contact performance of the interface, reduce interface defects and charge accumulation, thereby reducing interface impedance, helping to improve the transmission efficiency of ions and electrons, and improving the first coulomb efficiency of the battery. The uniform dispersion of inorganic materials in the polymer matrix formed by monomer polymerization can reduce agglomeration, thereby making the interface smoother. The smooth interface is conducive to reducing charge concentration and electric field distortion, and improving the cycle stability of the battery. The first polymerization can better combine the inorganic material with the polymer matrix formed by monomer polymerization to form a stable structure, which helps to enhance the mechanical properties of the interface softening layer, improve its ability to resist external forces and deformation, and improve the cycle performance of the battery. In addition, ultrasonic polymerization can also adjust the microstructure of the material and promote Li + The effective transport of ions in the ceramic phase, ceramic-polymer interface and intervening pathways helps to improve ionic conductivity and enhance the battery’s charge and discharge performance, thereby improving the battery’s safety, cycle performance and first coulombic efficiency.

[0058] According to some embodiments of the present invention, the temperature of the heated ultrasonic polymerization is 30°C-100°C. For example, it can be 30°C, 50°C, 70°C, 90°C, 100°C, etc. By limiting the temperature of the ultrasonic polymerization within the above range, the energy required for the reaction can be provided, making it easier for the molecules in the reaction system to collide and break chemical bonds, thereby improving the rate and efficiency of the polymerization reaction. According to other embodiments of the present invention, the temperature of the ultrasonic polymerization is preferably 40°C-60°C, for example, it can be 40°C, 50°C, 60°C, etc.

[0059] According to some embodiments of the present invention, the frequency of the heated ultrasonic polymerization is 0.5MHz-5.0MHz. For example, it can be 0.5MHz, 1MHz, 2MHz, 3MHz, 4MHz, 5MHz, etc. By limiting the frequency of ultrasonic polymerization within the above range, the ultrasonic wave can produce strong vibration and cavitation effects, which helps to promote the dispersion and uniform mixing of components such as monomers, initiators, lithium salts, inorganic fillers, conductive agents and cross-linking agents, and achieve high dispersion distribution, thereby promoting the uniform distribution of ectopic polymerization of each component material, helping to reduce the inhomogeneity of the polymerization product, and improving the consistency and stability of the material. The presence of uniformly distributed polymerization and inorganic materials can improve the contact performance of the interface, reduce interface defects and charge accumulation, thereby reducing interface impedance, helping to improve the transmission efficiency of ions and electrons, and improving the safety performance of the first coulomb efficiency of the battery. The uniform dispersion of inorganic materials in the polymer matrix of monomer polymerization can reduce agglomeration, thereby making the solid-solid contact interface smoother, and the smooth interface is conducive to reducing charge concentration and uniform deposition of lithium, inhibiting the generation of lithium dendrites, and improving the cycle stability of the battery. Thus, the safety performance, cycle performance and first coulomb efficiency of the battery can be improved.

[0060] According to some embodiments of the present invention, the time of the heated ultrasonic polymerization is 1h-12h. For example, it can be 1h, 3h, 5h, 10h, 12h, etc. By limiting the time of ultrasonic polymerization within the above range, on the one hand, it can give the monomer enough time to carry out the polymerization reaction, ensure that the monomer is fully converted into a polymer, improve the degree of polymerization, make the structure of the polymer matrix formed by the monomer polymerization more stable and complete, and be conducive to forming a uniform polymer network, enhance the mechanical properties and stability of the material, and thus improve the cycle performance of the battery. On the other hand, it can promote the better dispersion of inorganic materials and conductive agents in the polymer matrix formed by monomer polymerization, help to break the agglomeration of inorganic materials and conductive agents, make them evenly distributed in the polymer, improve the performance uniformity of the polymer matrix formed by monomer polymerization, and good dispersibility can reduce the interface impedance, improve the interface flatness, promote the effective transmission of lithium ions in the ceramic phase, ceramic-polymer interface and intervention path, improve the ionic conductivity and electrochemical stability window, and help improve the charge and discharge performance, cycle life and safety of the battery.

[0061] It should be noted that there is no particular limitation on the types of monomers and initiators, and those skilled in the art can flexibly select them according to needs.

[0062] As an example, the monomer includes a monomer with high ionic and electronic conductivity, for example, the monomer includes but is not limited to at least one of acrylate monomers, olefin nitrile monomers, cycloolefin monomers, vinylidene ester monomers, amide monomers, alkyl sulfide, sulfate monomers, borate monomers, cyanamide monomers and quaternary ammonium salt monomers.

[0063] As an example, the monomers include ethylene glycol methacrylate, ethylene glycol diacrylate, vinylene carbonate, vinylidene fluoride, tetrafluoroethylene, propylene carbonate polyvinylidene fluoride, acrylonitrile, ethylene oxide, vinylidene fluoride-hexafluoropropylene, hexafluoropropylene, lactam, dioxolane, dithiolane, lipoic acid, cyclosulfide, alkyl disulfide, tetrakis(hydroxymethyl)phosphonium chloride, melamine, olefinated monophosphine ligand, diphosphine ligand, arginine methyl ester, arginine ethyl ester, methoxy polyethylene glycol, isocyanate, quaternary ammonium salt monomer, boroxane , trifluoromethylphenylboronic acid methyliminodiacetate, phthalic acid diacrylate, pentaerythritol tetraacrylate, methacrylate, methacryloyloxyethyl, ethylene glycol acrylate, pentaerythritol acrylate, ethylene glycol methacrylate, ethylene glycol dimethacrylate, ethylene glycol dimethyl ether vinyl sulfite, vinylene trithiocarbonate, 1,3-propenyl-sultone, ethyl vinyl sulfone, vinyl acetate, acrylamide, 1,3-dioxolane and 1,4-dioxane.

[0064] As an example, the initiator includes at least one of 2,2'-azobis(isobutyronitrile), benzoyl peroxide, azobisisoheptanenitrile, diethylhexyl peroxydicarbonate, dimethyl azobisisobutyrate, dibenzoyl oxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, mercaptobenzene, thiolate and alkyl mercaptan.

[0065] According to some embodiments of the present invention, the step of mixing the monomer and the initiator, performing the first polymerization, and obtaining the prepolymer precursor solution includes: mixing the monomer, lithium salt, inorganic filler, conductive agent, crosslinking agent, initiator and solvent, and performing the first polymerization to obtain the prepolymer precursor solution. The monomer is the basis for forming the polymer. The polymer matrix is ​​constructed through polymerization reaction to provide structural support and certain physical and chemical properties for the pole piece. In the battery system, the main function of the lithium salt is to provide lithium ions to ensure that the battery has enough lithium ions for transmission during the charging and discharging process, thereby achieving the electrochemical performance of the battery. The inorganic filler can improve the mechanical strength and thermal stability of the pole piece, and synergize with the polymer matrix to improve the transmission efficiency of ions in the pole piece. The conductive agent can form a conductive network between the active substances, promote the transmission of electrons, reduce the internal resistance of the battery, and improve the charge and discharge performance and rate performance of the battery. The crosslinking agent promotes the crosslinking reaction between the polymer molecules, so that the polymer forms a three-dimensional network structure. The initiator initiates the polymerization reaction of the monomer to form a polymer. The solvent can dissolve the components so that they can be fully mixed and uniform. By mixing the above components and performing the first polymerization, a prepolymer precursor solution with a certain molecular weight and reaction activity can be obtained, which provides a basis for the subsequent second polymerization, so that the second polymerization can form a polymer matrix and an interface flexible layer in the active material layer.

[0066] According to some embodiments of the present invention, a binder is further added to the prepolymer precursor liquid, and the binder includes but is not limited to at least one of polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), polypropylene, polyethylene, polyvinylidene fluoride (PVDF), SBR rubber, fluorinated rubber, polyurethane, polyamide, sodium carboxymethyl cellulose (CMC) and polyacrylic acid.

[0067] According to some embodiments of the present invention, based on the total mass of the monomer, the initiator, the lithium salt, the inorganic filler, the conductive agent and the cross-linking agent, the mass proportion of the monomer is 0.5%-30%. For example, it can be 0.5%, 1%, 5%, 10%, 20%, 30%, etc. By limiting the mass proportion of the monomer to the above range, an effective polymerization reaction can be carried out under the action of the initiator, which helps to ensure the controllability of the polymerization process, avoid excessive monomers resulting in too low mechanical strength of the formed polymer matrix, and inability to composite inorganic fillers, and reduce the occurrence of side reactions in the system; at the same time, it also prevents too few monomers from causing insufficient polymerization products and inability to form an effective polymer matrix, thereby optimizing the performance of the interface flexible layer, so that it can better play the role of improving poor solid-solid contact and preventing micro short circuits and large-area short circuits, thereby improving the cycle stability and safety performance of solid-state batteries.

[0068] According to some embodiments of the present invention, based on the total mass of the monomer, the initiator, the lithium salt, the inorganic filler, the conductive agent and the cross-linking agent, the mass ratio of the lithium salt is 0.5%-30%. For example, it can be 0.5%, 1%, 5%, 10%, 20%, 30%, etc. The addition of lithium salt can increase the number of free lithium ions and reduce the glass transition temperature of the polymer matrix formed by the polymerization of monomers, thereby promoting the relaxation of polymer chains, and thus improving the ionic conductivity of the polymer matrix and promoting the migration of lithium ions. By limiting the mass ratio of lithium salt to the above range, it is possible to ensure smooth ion conduction, improve ionic conductivity, thereby improving the charge and discharge performance of the battery, and reduce the occurrence of side reactions, thereby improving the cycle life and safety of the battery.

[0069] As an example, the lithium salt includes at least one of lithium trifluoromethanesulfonate, lithium hexafluoroarsenate, lithium perchlorate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium hexafluorophosphate.

[0070] According to some embodiments of the present invention, based on the total mass of the monomer, the initiator, the lithium salt, the inorganic filler, the conductive agent and the cross-linking agent, the mass proportion of the inorganic filler is 5%-50%. For example, it can be 5%, 10%, 20%, 30%, 40%, 50%, etc. The introduction of inorganic fillers can reduce the crystallinity of the polymer matrix formed by monomer polymerization, increase the amorphous region, thereby increasing the migration rate of ions, and the inorganic filler has high thermal stability. By limiting the mass proportion of inorganic fillers to the above range, on the one hand, it can effectively improve the high-temperature thermal stability of the polymer matrix formed by monomer polymerization. When the battery generates heat during operation or charging and discharging, the inorganic filler can help disperse and conduct heat, reduce local overheating, thereby reducing the risk of thermal runaway and improving the safety and cycle performance of the battery. On the other hand, it can be evenly dispersed in the polymer matrix, interact with the polymer matrix and other components, improve the contact performance of the interface, promote the transmission of ions and electrons, and improve the electrochemical performance of the battery.

[0071] According to some embodiments of the present invention, the D50 particle size of the inorganic filler is 2nm-500nm. For example, it can be 2nm, 10nm, 50nm, 100nm, 200nm, 500nm, etc. By limiting the D50 particle size of the inorganic filler to the above range, the inorganic filler has good dispersibility, can be more evenly dispersed in the polymer matrix, can better interact with the polymer matrix and other components, improve interface performance, reduce interface impedance, improve interface flatness, promote the transmission of ions and electrons, and improve the electrochemical performance of the battery. According to some specific embodiments of the present invention, the Dv50 of the inorganic filler is preferably 10nm-300nm.

[0072] It should be noted that the D50 particle size refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%, and is measured using a laser particle size analyzer (eg, Malvern Master Size 3000) with reference to standard GB / T 19077-2016.

[0073] According to some embodiments of the present invention, the inorganic filler includes at least one of an inorganic active filler and an inorganic inert filler. The inorganic active filler can be used as an active material to provide lithium ions. The inorganic filler will destroy the aggregation structure of the polymer matrix, reduce the crystallinity, and increase the number of conductive polymer segments. There are many continuous defects in the low activation energy active filler, which makes it easy for the ions to jump. In addition, the active filler itself can provide a large amount of lithium ions, thereby increasing the concentration of free lithium ions at the interface between the active filler and the polymer to enhance ionic conductivity. When thermal runaway occurs in the battery cell, the inorganic active filler can delay the spread of heat and increase the time for the battery cell to fail, thereby providing the battery management system (BMS) with reaction time to take protective measures, which is beneficial to improving the safety performance of the battery.

[0074] It can be understood that in the embodiments of the present application, the inorganic inert filler refers to a substance that does not contain lithium and does not undergo chemical reactions in the battery, and the inorganic active filler refers to a substance that contains lithium.

[0075] The inorganic active filler includes at least one of oxide active fillers, sulfide active fillers, halide active fillers, nitride active fillers, boride active fillers and hydride active fillers; the oxide active filler includes at least one of garnet type active fillers, perovskite type active fillers, NASICON type active fillers and LISICON type active fillers; the garnet type active filler includes Li x1 LqCy y1 A1 z1 O 12 and Li x2 La 3-y2 B y2 Zrz2 O 12 At least one of the following, wherein Li x1 Ln3Z y1 A1 z1 O 12 Satisfies: 6≤x1≤7, 1≤y1≤2, 0≤z1≤0.5, A1 includes at least one of Ta, Nb, Mg, Ti, Te, W; Li x2 La 3-y2 B1 y2 Zr z2 O 12 Satisfying: 6≤x2≤7, 0≤y2≤0.5, 1≤z2≤2, B1 includes at least one of Ca, Rb, Al, and Ga; the perovskite active filler includes Li 3.3 La 0.53 TiO3、Li 3x3 La 2 / 3-x3 TiO3 and Li x4 Sr y3 M1 z3 At least one of TaO3, wherein Li 3x3 La 2 / 3-x3 TiO3 satisfies: 0≤x3≤2 / 3; the NASICON type active filler includes Li x5 Al y4 M2 z4 (PO4)3、Li x6 Y y5 Zr z5 At least one of Li(PO4)3, LiTi2(PO4)3, LiGe2(PO4)3 and LiGeTi(PO4)3, wherein Li x5 Al y4 M2 z4 (PO4)3 satisfies: 1.3≤x5≤1.5, 0.3≤y4≤0.5, 1.5≤z4≤1.7, M2 includes at least one of Ti, Ge, Hf, Zn, Zr and Si, Li x6 Y y5 Zr z5 (PO4)3 satisfies: 1.3≤x6≤1.5, 0.3≤y5≤0.5; the LISICON type active filler includes Li 3+x7 (P 1-x7 Si x7 )O4、Li 3+x8 Ge x8 V 1-x8 At least one of O4, wherein Li 3+x7 (P 1-x7 Si x7 )O4 satisfies: 1.5≤x7≤1.7, Li3+x8 Ge x8 V 1-x8 O4 satisfies: 0.25≤x8≤0.72; the sulfide active filler includes Argyrodite type LiPSM3X1, Thio-LiSICON type Li 4-x9 A2 1-x9 B2 x9 S4 and at least one of glassy sulfides, wherein LiPSM3X1 satisfies: M3 includes at least one of O, Cu, Zn, Bi, Sn, Al and In, X1 includes at least one of F, Cl, Br and I, Li 4-x9 A2 1-x9 B2 x9 S4 satisfies: 0≤x9≤0.5, A2 includes at least one of Si, Sn, Ge and Zr, B2 includes at least one of P, Al, Zn and Ga; the glassy sulfide includes at least one of Li2S-P2S5, Li2S-SiS2 and Li2S-B2S3; the halide active filler includes LiX2, Li2M4X34, Li3M5X46 and Li x10 M6 y6 Ln z6 Cl3, wherein LiX2 satisfies: X2 includes at least one of F, Cl, Br and I, Li2M4X34 satisfies: M4 includes at least one of Mg, Mn, Fe, Zn and Cd, X3 includes at least one of F, Cl, Br and I, Li3M5X46 satisfies: M5 includes at least one of O, In, Y, Yb, Sc, Ho and Er, X4 includes at least one of F, Cl, Br and I, Li x10 M6 y6 Ln z6 Cl3 satisfies: 0≤x10≤0.5, 0≤y6≤0.83, 0≤z6≤0.83, M6 includes at least one of Ta, Zr, Ca and Al, Ln includes at least one of La, Ce, Pr, Nd and Sm; the nitride active filler includes at least one of LiPON, Li3N, Li7PN4 and LiSi2N3; the boride active filler includes Li2B4O7, Li2O-B2O3-P2O5 and Li 6+2x11 [B 10 S 18 ]S x11 At least one of the following, wherein Li 6+2x11 [B 10 S 18 ]S x11The hydride active filler includes at least one of Li3AlH6, LiBH4, LiNH2, Li2NH, LiBH4-LiNH2, LiBHI, and LiBH4-LiX5, and LiBH4-LiX5 satisfies: X5 includes at least one of Cl, Br, and I; the inorganic inert filler includes an oxide inert filler, a nitride inert filler, a boride inert filler, a halide inert filler, a dielectric ceramic inert filler, a ferroelectric ceramic inert filler, and a The inert filler comprises at least one of an inert filler, a piezoelectric ceramic inert filler, a diatomaceous earth inert filler, a mullite inert filler, a montmorillonite inert filler and a kaolin inert filler; the oxide inert filler comprises at least one of silicon oxide, boron oxide, magnesium oxide, copper oxide, nickel oxide, calcium oxide, aluminum oxide, titanium oxide, zirconium oxide, vanadium oxide, lanthanum oxide, beryllium oxide, yttrium oxide, cerium oxide and lead zirconium titanate; the nitride inert filler comprises at least one of silicon nitride, titanium nitride, aluminum nitride, boron nitride, magnesium nitride, zirconium nitride and silicon oxynitride.

[0076] It should be noted that NASICON-type active filler refers to active materials with a sodium superion conductor (Na Super Ionic Conductor, NASICON) structure, a three-dimensional open framework structure composed of metal ions and polyhedrons; LISICON-type active filler refers to a class of materials with a lithium superion conductor (Lithium Super Ionic Conductor, LISICON) structure; Argyrodite type has a unique crystal structure, generally composed of chalcogen elements (such as sulfur, selenium, tellurium, etc.) and metal elements, and its structure contains an open framework structure.

[0077] According to some embodiments of the present invention, the mass percentage of the initiator to the mass percentage of the monomer is 0.1%-3%. For example, it can be 0.1%, 0.5%, 1%, 2%, 3%, etc. By limiting the mass percentage of the initiator to the above range, the occurrence of problems such as free radical transfer to the solvent and double radical termination during free radical polymerization can be reduced, thereby improving the stability of the polymerization reaction, reducing the occurrence of side reactions such as oxidative decomposition, ensuring the quality and stability of the polymer, and synergizing well with other components such as monomers, lithium salts, inorganic fillers, conductive agents and cross-linking agents to jointly construct a stable polymer matrix structure, which helps to optimize the performance of the polymer matrix and improve the comprehensive performance of the pole piece, thereby helping to improve the cycle stability and safety performance of the battery.

[0078] According to some embodiments of the present invention, the D50 particle size of the conductive agent is 5nm-1000nm, for example, it can be 5nm, 10nm, 50nm, 100nm, 500nm, 1000nm, etc. By limiting the D50 particle size of the conductive agent to the above range, the conductive agent has high conductivity and good dispersibility, and can be more evenly distributed in the polymer matrix. The uniform distribution can ensure the uniform conduction of current in the pole piece, avoid the generation of hot spots and dead lithium caused by excessive local current, and improve the cycle stability of the battery.

[0079] As an example, the conductive agent includes at least one of conductive graphite, conductive carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, graphene, silicon carbide, boron carbide, silicon boride, vanadium boride, magnesium boride, titanium boride, 6-amino-1-hexanol-polyacrylic acid ion crosslinked polymer, hydroxyethylethylenediamine-polyacrylic acid ion crosslinked polymer, diglycolamine-polyacrylic acid ion crosslinked polymer, 5-amino-1-pentanol-polyacrylic acid ion crosslinked polymer, 4-amino-1-butanol-polyacrylic acid ion crosslinked polymer, and N,N-bis(2-hydroxyethyl)ethylenediamine-polyacrylic acid ion crosslinked polymer. The introduction of the conductive agent can improve the conductivity of the polymer matrix, build an efficient electron transport network, reduce the internal resistance of the battery, and improve the charge and discharge efficiency of the battery.

[0080] As an example, the crosslinking agent includes isocyanate, propylenediamine, polyethylene glycol, polypropylene glycol, trimethylolpropane, trimethylolethane, polypropylene glycol glycidyl ether, zinc oxide, aluminum chloride, aluminum sulfate, sulfur, boric acid, borax, chromium nitrate, styrene, α-methylstyrene, acrylonitrile, acrylic acid, methacrylic acid, glyoxal, aziridine, tetraethyl orthosilicate, methyl orthosilicate, trimethoxysilane, p-toluenesulfonic acid, p-toluenesulfonyl chloride, diisopropylbenzene peroxide, di-2,4-dichlorobenzoyl peroxide, aluminum isopropoxide, zinc acetate, titanium acetylacetonate, polycarbodiimide (preferably when combined with a conductive agent), acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, methacrylic acid, hydroxyethyl methacrylate, hydroxypropyl methacrylate, divinylbenzene, N-hydroxymethyl acrylamide, and diacetone acrylamide. Preferably, the crosslinking agent is ethyl orthosilicate, methyl orthosilicate, trimethoxysilane, polycarbodiimide, ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate, tetraethylene glycol diacrylate, 1,3-propylene glycol dimethacrylate, 1,2-propylene glycol dimethacrylate, 1,3-propylene glycol di ... One or more of alcohol esters, 1,2-propylene glycol diacrylate, 1,4-butylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol diacrylate, 1,3-butylene glycol diacrylate, pentaerythritol diacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate, more preferably at least one of triethylene glycol dimethacrylate, triethylene glycol diacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate. The addition of a crosslinking agent forms chemical bonds to connect the polymer chains, thereby enhancing the mechanical properties, thermal stability and electrochemical properties of the polymer matrix.

[0081] As an example, the solvent includes but is not limited to at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, nitrogen methyl pyrrolidone, fluoroethylene carbonate, acetonitrile, dimethyl sulfoxide, dimethylformamide chloroform, ethyl acetate, N,N-dimethylformamide and N,N-dimethylacetamide and tetrahydrofuran.

[0082] S2, introducing the prepolymerized precursor solution into at least one side of the current collector, and performing a second polymerization to form an interface flexible layer on at least one side of the current collector.

[0083] In this step, the prepolymerized precursor solution is introduced into at least one side of the current collector and then a second polymerization reaction is performed, so that an interface flexible layer can be formed on at least one side of the current collector.

[0084] According to some embodiments of the present invention, the temperature of the second polymerization is 40°C-120°C. For example, it can be 40°C, 60°C, 80°C, 100°C, 120°C, etc. By limiting the temperature of the second polymerization to the above range, it is possible to provide sufficient energy for the second polymerization, accelerate the polymerization reaction of the monomer, control the degree of the second polymerization, achieve better combination of the prepolymer precursor liquid and the active material, form a stable active material layer and an interface flexible layer, reduce the structural collapse, particle rupture, and metal ion dissolution of the active material during the charge and discharge process, and improve the cycle life and safety of the battery.

[0085] According to some embodiments of the present invention, the second polymerization time is 10s-2min. For example, it can be 10s, 40s, 1min, 2min, etc. By limiting the time of the second polymerization to the above range, the degree of the second polymerization can be accurately controlled, which helps to form a uniform and stable active material layer and an interface flexible layer, which can reduce the shedding and deformation of the active material during the charge and discharge process, and improve the cycle life and safety of the battery.

[0086] There is no particular limitation on the method of introduction, which includes but is not limited to at least one of coating, spraying and dipping. Those skilled in the art can flexibly select the method according to their needs.

[0087] According to a specific embodiment of the present invention, the introduction method includes coating, and the coating includes gravure coating. Gravure coating can accurately control the thickness and uniformity of the coating, achieve a uniform coating effect, ensure the distribution consistency of the active material and the prepolymer precursor solution on the current collector, make the battery react more uniformly in various parts during the charge and discharge process, reduce the risk of local overcharge, over discharge or overheating, improve the consistency and reliability of the battery, reduce problems caused by local performance differences, and improve the safety performance and cycle stability of the battery.

[0088] It should be noted that gravure coating is mainly composed of an unwinding device, a coating head, a drying device, a winding device, etc. The process flow of gravure coating includes: placing the current collector to be coated on the unwinding device, adjusting the unwinding tension to keep the current collector flat; pouring the coating into the material trough of the coating head, and starting the coating head. During the rotation of the gravure roller, the coating is transferred from the material trough to the mesh on the surface of the gravure roller. The metering roller contacts the gravure roller and accurately measures the thickness of the coating. The scraper scrapes off the excess coating on the surface of the gravure roller to ensure that the coating thickness is uniform. When the current collector passes through the coating head, the coating on the gravure roller is transferred to the current collector to complete the coating process. The coated current collector enters the drying device, and the solvent in the coating is evaporated by hot air drying or infrared drying, so that the coating is solidified on the current collector. The temperature and wind speed of the drying device need to be adjusted according to the properties of the coating and the drying requirements to ensure that the coating is dried evenly without bubbling, cracking and other problems. The dried current collector enters the winding device, and the winding tension is adjusted to keep the current collector flat. The winding device collects the coated current collector to complete the entire coating process.

[0089] According to some embodiments of the present invention, the speed of the gravure coating is 0.5m / min-10m / min. For example, it can be 0.5m / min, 1m / min, 3m / min, 5m / min, 10m / min, etc. By limiting the speed of the gravure coating within the above range, the gravure coating can better ensure the uniform distribution of the active material and the prepolymer precursor solution on the current collector, so that the reaction of each part of the battery during the charge and discharge process is more uniform, reducing the risk of local overcharge, over discharge or overheating, improving the consistency and reliability of the battery, reducing the problems caused by local performance differences, and improving the safety performance and cycle stability of the battery.

[0090] According to some embodiments of the present invention, the tension of the gravure coating is 30N-200N. For example, it can be 30N, 50N, 100N, 150N, 200N, etc. Appropriate tension can keep the current collector flat during the coating process, avoid undesirable phenomena such as wrinkles and waves, and ensure the uniformity and thickness accuracy of the coating. Appropriate tension can also increase the adhesion between the current collector and the coating. The tension makes the current collector in close contact with the gravure roller, which helps the coating to better adhere to the current collector and improve the reliability and cycle stability of the battery.

[0091] According to some embodiments of the present invention, the coating thickness of the gravure coating is 0.5 μm-3 μm. For example, it can be 0.5 μm, 1 μm, 2 μm, 3 μm, etc. By limiting the coating thickness of the gravure coating to the above range, the loading amount of the active material can be ensured while maintaining the stability of the pole piece structure, and the mechanical strength and ion transport performance of the pole piece can be balanced to a certain extent, thereby extending the cycle life of the battery.

[0092] Furthermore, when gravure coating is used, secondary thermal polymerization can be achieved during the drying process, which can further polymerize the prepolymer precursor liquid and the active material, increase the degree of polymerization, increase the molecular weight and cross-linking degree of the polymer, and enable the pole piece to better withstand the volume change and stress during the charge and discharge process during use, reduce the shedding and structural damage of the active material, thereby improving the cycle life and performance stability of the battery. Secondary thermal polymerization can also make the coating cure more evenly, reduce surface unevenness and defects, improve the surface flatness of the pole piece, fill pores, and help increase the contact area and tightness between the pole piece and the electrolyte, reduce interface impedance, improve ion transmission efficiency, reduce the risk of short circuits during battery assembly and use, and improve battery safety.

[0093] It should be noted that in the process of gravure coating, the coating method is continuous coating, intermittent coating or zebra coating, the coating size accuracy is ≤±0.3mm, the coating thickness accuracy is ±0.3um, and the oven temperature accuracy is ±2°C.

[0094] According to some embodiments of the present invention, before the step of mixing the monomer and the initiator, performing the first polymerization, and obtaining the prepolymer precursor liquid, it also includes: preparing an active material layer on at least one side of the current collector. Specifically, the active material is first prepared into an active slurry, and then introduced into at least one side of the current collector. After the active material layer is formed, the prepolymer precursor liquid is introduced into the side of the active material layer away from the current collector, so that the prepolymer precursor liquid can be filled into the active material layer. During the second polymerization reaction, the prepolymer precursor liquid can be polymerized and cured in the pole piece, reducing the defects and pores inside the pole piece, preventing the occurrence of micro short circuits, and preventing direct contact between the positive and negative electrodes, thereby preventing the occurrence of large-area short circuits, and improving the safety performance and cycle stability of the battery.

[0095] It should be noted that the process of preparing the active substance into an active slurry usually involves mixing, stirring, grinding, etc. the active substance with other ingredients such as a solvent and a binder to obtain a uniform slurry system. The present invention does not specifically limit the types of active substances, solvents, and binders, and those skilled in the art can flexibly select them based on existing ones.

[0096] As an example, the binder includes but is not limited to at least one of polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), polypropylene, polyethylene, polyvinylidene fluoride (PVDF), SBR rubber, fluorinated rubber, polyurethane, polyamide, sodium carboxymethyl cellulose (CMC) and polyacrylic acid.

[0097] As an example, the active material includes one of a positive electrode active material and a negative electrode active material, wherein the positive electrode active material includes but is not limited to at least one of a nickel-cobalt-manganese ternary material, a nickel-cobalt-aluminum ternary material, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium vanadium phosphate, and a lithium-rich manganese-based material.

[0098] As an example, the negative electrode active material includes but is not limited to at least one of graphite, graphene, soft carbon, hard carbon, elemental silicon, silicon-oxygen materials, silicon-carbon materials, silicon-nitrogen composite materials, silicon-based alloys, elemental tin, tin oxide compounds, tin-based alloys, lithium metal, lithium alloy negative electrode, lithium titanium oxide, transition metal oxide and transition metal sulfide.

[0099] According to some embodiments of the present invention, after the monomer and the initiator are mixed and the first polymerization is performed to obtain the prepolymer precursor liquid, the prepolymer precursor liquid is introduced into at least one side of the current collector and the second polymerization is performed to form an interfacial flexible layer on one side of the current collector, and the prepolymer precursor liquid is mixed with the active substance. Specifically, after the prepolymer precursor liquid and the active substance are mixed, they are introduced into the surface of the current collector for a second polymerization reaction. Through the one-step construction method, the combination of the prepolymer precursor liquid and the active slurry, and the process of the secondary polymerization, it is helpful to form a good conductive and lithium conductive channel, and improve the charge and discharge performance and efficiency of the battery. In the process of the second polymerization, volatile components such as solvents can be removed, and residual monomers can be further reacted to reduce their negative impact on battery performance, effectively improve the degree of polymerization, reduce the water content (<100ppm), and prevent problems such as uneven surface density caused by excessive polymerization speed. Furthermore, the active substance can be prepared into an active slurry, added to the prepolymer precursor liquid for mixing, and then introduced into at least one side of the current collector for a second polymerization reaction.

[0100] As an example, the active material includes one of a positive electrode active material and a negative electrode active material.

[0101] As an example, the positive electrode active material includes at least one of a nickel-cobalt-manganese ternary material, a nickel-cobalt-aluminum ternary material, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium vanadium phosphate and a lithium-rich manganese-based material.

[0102] As an example, the negative electrode active material includes at least one of graphite, graphene, soft carbon, hard carbon, elemental silicon, silicon-oxygen material, silicon-carbon material, silicon-nitrogen composite material, silicon-based alloy, elemental tin, tin oxide, tin-based alloy, lithium metal, lithium alloy, lithium titanium oxide, transition metal oxide and transition metal sulfide.

[0103] According to some embodiments of the present invention, after the prepolymer precursor liquid is introduced into at least one side of the current collector, a second polymerization is performed to form an interface flexible layer on at least one side of the current collector, and then a liquid injection operation is also included. Specifically, the pole piece roll obtained by gravure coating is injected with liquid, and the injected pole piece roll is placed in an oven for curing at a temperature of 50°C-80°C and a curing time of 3h-12h. The solvent in the pole piece can be evaporated by curing to form a gel electrolyte. Finally, the cured pole piece roll is dried at a temperature of 60°C-120°C and a drying time of 3h-10h.

[0104] It should be noted that the specific operation of liquid injection is not particularly limited, and those skilled in the art can flexibly select it as needed. Further, the liquid used in the liquid injection process includes an electrolyte, and the type of the electrolyte is not particularly limited, and those skilled in the art can flexibly select it as needed.

[0105] According to some embodiments of the present invention, the method further includes preparing a solid electrolyte layer on the interface flexible layer. Specifically, after the preparation of the active material layer and the interface flexible layer is completed, the solid electrolyte layer is continued to be added at a specific position to improve the overall structure of the solid-state battery. The presence of the solid electrolyte layer provides a dedicated channel for the transmission of lithium ions in the battery. It has a high ionic conductivity, which can promote the rapid migration of lithium ions between the positive and negative electrodes and improve the charge and discharge performance of the battery. Compared with traditional liquid electrolytes, solid electrolytes can reduce the risk of leakage and improve the safety of the battery.

[0106] It should be noted that there is no special limitation on the raw material components of the solid electrolyte layer, and the use of conventional raw material components in the field belongs to the inventive concept of the present application, and technicians in the field can flexibly select them according to needs.

[0107] According to the preparation method of the embodiment of the present invention, the heterotopic polymerization technology is used, and the first polymerization reaction can realize the controllable heterotopic polymerization process of the monomer, ensure the stable polymerization reaction, improve the consistency of product quality, and use ultrasonic polymerization in the thermal polymerization process to achieve high dispersion of the monomer in the polymerization system, laying the foundation for the construction of high-flux ion transmission channels, which helps to improve the ion conductivity of the battery, thereby improving the charge and discharge efficiency. It can also achieve controllable molecular weight of the polymerization product, achieve uniform solidification, and ensure the stability of battery performance.

[0108] Furthermore, by adding inorganic fillers and combining them with ultrasonic polymerization, the heterogeneous polymerization of each component material can be evenly distributed, ensuring the consistency of the material at the microscopic level and avoiding local performance differences, thereby improving the stability of the overall performance and reducing the interface impedance. Reducing the interface impedance can promote the transmission of ions and electrons and improve the charge and discharge efficiency of the battery. At the same time, improving the flatness of the interface helps to reduce defects and unevenness at the interface, further reducing impedance and improving battery performance. The first polymerization reaction can improve the mechanical properties and electrochemical stability of the interface softening layer. When using ultrasonic polymerization, the degree of polymerization of the monomer can be precisely controlled, which can improve the ion transmission channel and promote Li + Effective transmission in the ceramic phase, ceramic-polymer interface and intervention path improves ion conductivity, thereby improving the battery's charge and discharge efficiency and power output. In addition, the effect of ultrasound can make the particles more evenly dispersed and avoid agglomeration, thereby improving the mechanical strength and stability of the pole piece. At the same time, evenly dispersed particles also help improve ion transmission efficiency and further improve battery performance.

[0109] Furthermore, the first polymerization process is combined with ultrasonic polymerization to achieve high dispersion of inorganic fillers and conductive agents. High dispersion ensures that the inorganic fillers and conductive agents are evenly distributed in the pole piece, avoiding local aggregation and inhomogeneity, and can form a continuous ion and electron transmission pathway in the pole piece, wherein the polymer structure formed in the first polymerization process can provide a channel for ion transmission, while the highly dispersed inorganic active fillers and conductive agents facilitate the transmission of electrons. The combination of the two achieves rapid ion / electron transmission and improves battery performance. In the pole piece composite process, the first polymerization process is combined with ultrasonic polymerization to regulate the degree of monomer polymerization on the pole piece surface, thereby adjusting the physical and chemical properties of the pole piece and improving the cycle life and safety of the battery.

[0110] Furthermore, the prepolymer precursor liquid is introduced into at least one side of the current collector by gravure coating to compound the pole piece, and a diaphragm-free battery is prepared, which simplifies the battery structure and reduces the cost. The problem of poor solid-solid contact is improved by softening the interface, reducing the interface impedance, and improving the cycle stability of the battery. After being introduced into the surface of the pole piece, the prepolymer precursor liquid can enter the inside of the pole piece and solidify inside the pole piece. The solidified prepolymer precursor liquid can fill the pores and defects in the pole piece, reduce the risk of micro-short circuits, and prevent large-area short circuits caused by direct contact between the positive and negative electrodes after thermal runaway occurs, thereby improving the safety and cycle performance of the battery.

[0111] Furthermore, the use of pole piece composite and interface softening technology can build all-solid-state battery pole pieces in one step, simplifying the production process and improving production efficiency. Compared with the traditional multi-step preparation method, this one-step construction method reduces the errors and losses that may be caused by the intermediate links, and ensures the quality and performance stability of the pole piece. This one-step construction method can make the prepolymer precursor liquid achieve high dispersion and uniform distribution inside and on the surface of the pole piece at the same time. Inside the pole piece, the uniform distribution of the prepolymer precursor liquid can improve the structural stability and ion transmission performance of the active material. On the surface, the uniformly distributed prepolymer precursor liquid can improve the contact with the solid electrolyte, reduce the interface impedance, promote ion transmission, and construct an ion / electron transmission pathway. The ion transmission pathway ensures the rapid migration of lithium ions between the pole piece and the solid electrolyte, and improves the charge and discharge efficiency and rate performance of the battery. The electron transmission pathway ensures the efficient transmission of electrons in the internal and external circuits of the pole piece, reduces the internal resistance of the battery, and improves the energy conversion efficiency. This technology is also applicable to conductive agents, that is, the pole piece composite and interface softening technology can make the conductive agent achieve high dispersion and uniform distribution inside and on the surface of the pole piece, improve the utilization rate of the conductive agent, and reduce the internal resistance of the battery. Therefore, the electrode composite and interface softening technology achieves highly dispersed and uniform distribution of the prepolymer precursor liquid, inorganic filler and conductive agent inside and on the surface of the electrode, constructs an ion / electron transmission pathway, and effectively improves the electrochemical performance of the battery.

[0112] Furthermore, the application of the pole piece preparation technology of the present invention in lithium batteries improves the penetration of the microporous structure of the battery core and the uniformity of the macroscopic distribution of the polymer inside the battery, and solves the problems of uneven polymerization and uneven wetting during the in-situ curing process. The battery prepared by this method has high ionic conductivity and electrochemical stability window, high mechanical strength and stable cycle performance and excellent safety performance. In addition, this method has low cost, high efficiency, can effectively control the consistency of the product, and has a stable yield, which is conducive to large-scale production and development.

[0113] In the second aspect of the present invention, the present invention provides a pole piece 10 prepared by heterogeneous polymerization. According to an embodiment of the present invention, the pole piece includes a pole piece prepared by the method of the first aspect, Figure 1 The pole piece includes a current collector 1, an active material layer 2 and an interface flexible layer 3.

[0114] The main function of the current collector 1 is to carry active substances and collect the current generated by the electrochemical reaction to achieve the conversion of chemical energy into electrical energy. There is no special limitation on the material of the current collector, and those skilled in the art can select it according to needs.

[0115] According to an embodiment of the present invention, the active material layer 2 is disposed on at least one side of the current collector 1 , and the interface flexibility layer 3 is disposed on a side of the active material layer 2 away from the current collector 1 .

[0116] According to the pole piece of the above embodiment of the present invention, the active material layer is composed of a polymer matrix formed by polymerization of monomers and an active material, and is arranged on one side of the current collector. The polymer matrix formed by polymerization of monomers can fill in the gaps of the active material, which can ensure the effective contact between the active material and the current collector, thereby improving the transmission efficiency of electrons. The interface flexibility layer is composed of a polymer matrix formed by polymerization of monomers, and is located on the side of the active material layer away from the current collector. The interface softening of the interface flexibility layer can improve the problem of poor solid-solid contact, reduce the interface impedance, thereby improving the ion transmission efficiency, and can also alleviate the interface stress caused by the volume change during the battery charging and discharging process, enhance the stability of the pole piece structure, and then improve the cycle stability of the battery. In addition, since the active material will release oxygen when working under high voltage, the release of oxygen can also be suppressed by softening the interface, thereby improving the thermal stability and safety of the battery. The polymer matrix is ​​composed of monomers and initiators, which helps to form a uniform polymer matrix in the active material layer and the interface flexible layer. Through ectopic polymerization, during the electrode composite process, a high-flux ion transmission channel can be constructed to achieve a high dispersion effect of the monomer, form a uniform polymer matrix, and achieve uniform distribution in the active material layer and the interface flexible layer, thereby enhancing the stability of the electrode structure and greatly improving the safety of the battery. The interface flexible layer covers the active material layer, reducing the specific surface area of ​​the active material layer, thereby making the SEI film formed during the first charge and discharge smoother, reducing side reactions and effectively improving the first coulomb efficiency of the battery. Therefore, the electrode provided by the present application can improve the cycle stability, first coulomb efficiency and safety performance of the battery.

[0117] According to some embodiments of the present invention, the pole piece further comprises a solid electrolyte layer 4, and the solid electrolyte layer 4 is arranged on a side of the interface flexible layer 3 away from the active material layer 2. The solid electrolyte layer 4 can isolate the positive and negative electrodes, avoid the positive and negative electrodes from directly contacting each other and causing a short circuit, improve the safety of the battery, reduce the risk of safety accidents such as battery combustion and explosion, and make the battery safer and more reliable during use. In addition, the solid electrolyte also plays a supporting role to ensure the stability of the battery.

[0118] In a third aspect of the present invention, the present invention provides a solid-state battery. According to an embodiment of the present invention, the solid-state battery comprises a pole piece prepared by heterogeneous polymerization in the first aspect or a pole piece prepared by the method in the second aspect. The solid-state battery has excellent safety performance, cycle performance and first coulombic efficiency.

[0119] In a fourth aspect of the present invention, the present invention provides a diaphragm-free battery. According to an embodiment of the present invention, the diaphragm-free battery comprises a pole piece prepared by ex situ polymerization in the first aspect or a pole piece prepared by the method in the second aspect. The diaphragm-free battery has excellent safety performance, cycle performance and first coulombic efficiency.

[0120] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.

[0121] Example 1

[0122] 1. Preparation of pole piece:

[0123] 1) Dissolve the monomer, lithium salt, inorganic material, conductive agent, initiator and cross-linking agent in a solvent and stir evenly to form a solution, wherein the monomer mass accounts for 15%, the mass of the initiator is 1% of the monomer mass, the mass of the lithium salt accounts for 15%, the mass of the inorganic filler accounts for 25%, the monomer is ethylene glycol methacrylate, the lithium salt is lithium trifluoromethanesulfonate, and the inorganic filler is Li 3.3 La 0.53 TiO3, the conductive agent is conductive graphite, the initiator is 2,2'-azobis(isobutyronitrile), the crosslinking agent is isocyanate, and the solvent is dimethyl carbonate;

[0124] 2) transferring the solution prepared in step 1) to an ultrasonic device, and polymerizing the solution for the first time by heating ultrasound to obtain a prepolymer precursor solution, wherein the temperature of the heating ultrasound is 50° C., the frequency of the ultrasonic polymerization is 2 MHz, the time is 6 h, the degree of polymerization of the prepolymer precursor solution is 30%, and the viscosity of the prepolymer precursor solution is η=500 Pa·s;

[0125] 3) The positive electrode active material NCM811, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone, and the mass ratio of the three is 96:2:2), and then coated on the surface of the current collector, dried, and rolled for standby use to obtain a pole piece, and the prepolymer precursor liquid prepared in step 2) is uniformly coated on the pole piece by gravure coating, and the solvent on the surface of the pole piece is completely evaporated by an oven before winding, wherein the gravure coating parameters are: speed of 5m / min, tension of 100N, coating thickness of 1.5μm, oven temperature (second polymerization temperature) of 80°C, drying time of 1min, coating method of continuous, intermittent or zebra coating, coating size accuracy of ≤±0.3mm, coating thickness accuracy of ±0.3um, oven temperature accuracy of ±2°C, to obtain a positive pole piece prepared by heterogeneous polymerization;

[0126] 2. Preparation of solid-state batteries: Assemble the above-obtained positive electrode sheets with solid electrolytes and negative electrode sheets into a diaphragm-free battery, wherein the preparation method of the negative electrode sheet is to mix graphite, conductive carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a weight ratio of 93:2:3:2, add water and stir to form a uniform slurry, apply the slurry on a 10 μm copper foil current collector, control the surface density of the negative electrode so that the N:P ratio of the positive and negative electrodes (the capacity ratio of the positive electrode material to the negative electrode material per unit area) is 1.1:1, vacuum dry at 100°C, and obtain the negative electrode sheet by rolling and slitting.

[0127] The solid electrolyte is introduced onto the surface of the constructed positive electrode plate and / or negative electrode plate by coating or spraying, and the solid electrolyte solution is coated on the side of the positive electrode active material layer of the positive electrode plate away from the positive electrode current collector and dried to form a solid electrolyte layer, thereby obtaining a first electrode plate assembly including a stacked positive electrode plate and a solid electrolyte layer, wherein the thickness of the solid electrolyte layer is 10 μm.

[0128] Embodiment 14

[0129] The difference between Example 14 and Example 1 is that: a step is added in the process of preparing the electrode: the electrode roll obtained in step 3) is injected with liquid, and then placed in an oven for curing at a curing temperature of 60°C and a curing time of 6 hours, and then dried at a drying temperature of 90°C and a drying time of 7 hours, and the obtained electrode roll is rolled and die-cut to obtain a positive electrode, wherein the injected liquid is 1 mol of lithium hexafluorophosphate dissolved in a solvent with a mass ratio of EC:DEC:DMC=1:1:1.

[0130] Embodiment 15

[0131] The difference between Example 15 and Example 1 is that the thickness of the electrode obtained by ectopic polymerization containing inorganic fillers is controlled within the range of 10-80 μm, and a solid electrolyte layer is not required, and the interface flexible layer obtained by polymerization can serve as a solid electrolyte layer.

[0132] Example 16

[0133] The difference between Example 16 and Example 1 is that no inorganic material is added to the prepolymer precursor solution, and the rest is consistent with Example 1.

[0134] The pole pieces of Examples 2-13 are the same as those of Example 1 except for the experimental parameters (see Table 1).

[0135] Some experimental parameters of the electrode pieces in the preparation process of Examples 1-13 are shown in Table 1.

[0136] Table 1

[0137]

[0138]

[0139] Comparative Example 1

[0140] The difference between Comparative Example 1 and Example 1 is that the electrode obtained in Comparative Example 1 does not have an interface flexible layer and a polymer matrix formed by polymerization of monomers, and the rest is consistent with Example 1.

[0141] Comparative Example 2

[0142] The difference between Comparative Example 2 and Example 1 is that the monomer, lithium salt, inorganic filler, conductive agent, initiator and cross-linking agent are dissolved in a solvent, stirred evenly to form a solution, and then coated on at least one side of the current collector after complete polymerization.

[0143] Comparative Example 3

[0144] The difference between Comparative Example 3 and Example 1 is that the monomer, lithium salt, inorganic filler, conductive agent, initiator and cross-linking agent are dissolved in a solvent, stirred evenly to form a solution, and the obtained solution is directly coated on at least one side of the current collector, and then polymerized.

[0145] Testing and analysis

[0146] Under the same conditions, the batteries prepared in the above Examples 1-16 and Comparative Examples 1-3 were subjected to impedance, initial coulombic efficiency, cycle performance and safety performance tests. The specific test methods are as follows:

[0147] First coulombic efficiency and cycle performance test: In a glove box containing argon, the positive and negative battery shells, stainless steel gaskets, spring sheets, positive electrode sheets, and negative electrode sheets are assembled into button batteries. The negative electrode sheet is 150um thick metal lithium, and the positive electrode sheet is the above-prepared electrode sheet. After the button battery is assembled, it is left to stand at 25°C for 6 hours, and then a constant current charge and discharge mode test is performed using a charge and discharge instrument model CT2001A purchased from Wuhan Blue Electric Electronics Co., Ltd. - the battery is first charged, and the battery charge cutoff voltage is 4.2V, followed by discharge, and the discharge cutoff voltage is 2.75V, and the test temperature is 25°C. The battery charge and discharge test first performs 2 cycles of cycle activation at a rate of 0.1C, and then performs a long cycle at a rate of 0.5C. Record the first charge and discharge capacity, calculate the first coulombic efficiency, and record the capacity retention rate after the battery is cycled 500 times.

[0148] Interface impedance: The button cell prepared above (before cycle test) was tested for AC impedance in an electrochemical workstation using the AC impedance method, with the voltage amplitude set to 5 mV and the frequency range of 0.1 Hz to 1 MHz.

[0149] Safety performance test: The prepared positive electrode, solid electrolyte, and negative electrode are assembled into a 10Ah soft-pack battery. After injection, it is immersed at 45°C for 12 hours, and then subjected to a needle puncture test after hot pressing. Before the test, the battery is charged to a cut-off voltage of 4.2V at a constant current and constant voltage rate of 0.33C, and left to stand for 1 hour. The test is carried out in an explosion-proof box. The needle parameters used are a 3mm steel needle, a needle tip cone angle of 45 (the needle surface is smooth, free of rust, oxide layer, and oil), and a puncture speed of 0.1mm / s, and the battery cell is pierced until it penetrates. After penetration, let it stand for 1 hour. If the battery does not catch fire or explode, it passes, otherwise it fails.

[0150] The test results are shown in Table 2.

[0151] Table 2

[0152]

[0153]

[0154] “ / ” means none.

[0155] Combining Table 1 and Table 2, it can be seen that compared with the batteries of Comparative Examples 1-3, the battery interface impedance of Examples 1-15 is greatly reduced, and the first coulomb efficiency and 500-cycle capacity retention rate are significantly improved. When the inorganic filler ratio is ≥25% or the monomer polymerization is complete, the needle puncture test is passed, effectively improving the safety performance of the battery cell.

[0156] Compared with Comparative Examples 2 and 3, Example 1 does not use the heterogeneous polymerization method to prepare the positive electrode plate, which will result in uneven polymerization of the polymer monomers, thereby affecting the wettability of the polymer inside the plate, and failing to effectively fill the pores and defects in the plate, increasing the risk of micro-short circuits, which will lead to a significant decrease in battery safety and also affect the battery cycle performance.

[0157] Compared with Example 16, Examples 1-15 cannot suppress the occurrence of thermal runaway without adding inorganic fillers, resulting in a significant decrease in battery safety and also affecting the battery's cycle performance.

[0158] Compared with Example 1, in Examples 2 and 3, when the proportion of polymer is too small, the proportion of inorganic components increases, resulting in an increase in the specific surface area of ​​the particles on the electrode surface, the flatness of the formed SEI decreases, more lithium ions are consumed, resulting in a decrease in the first coulomb efficiency, and the solid-solid interface contact impedance increases, resulting in a decrease in long-cycle performance; when the proportion of polymer is too large, the interface impedance, first coulomb efficiency, and long cycle are basically the same, but the material cost is greatly increased.

[0159] Compared with Example 1, when the proportion of inorganic filler in Examples 4 and 5 is too low, the occurrence of thermal runaway cannot be effectively suppressed, resulting in a significant decrease in battery safety. When the proportion of inorganic filler is too high, the performance is significantly reduced as in Example 2.

[0160] Compared with Example 1, Examples 6, 7, 8, and 9 show that when the monomer prepolymerization degree is low, the viscosity of the composite slurry is too low, and the inorganic filler therein cannot exist in a highly dispersed form, and will agglomerate, and cannot smoothly enter the interior of the electrode and be evenly distributed, resulting in obstruction of the ion transmission channel and the generation of dead lithium, thereby affecting the electrochemical performance and safety performance of the battery; when the monomer prepolymerization degree is too high, the prepolymer molecular weight is too high, and it is blocked when entering the interior of the electrode, the ion and electron channels are incompletely constructed and unevenly distributed, thereby increasing the solid-solid contact impedance and affecting the coulomb efficiency and long cycle performance.

[0161] Compared with Example 1, in Examples 10 and 11, when the ultrasonic frequency is too low, the ultrasonic time is greatly increased to achieve the desired polymerization degree. If the time is too long, more monomers will volatilize, the final polymer ratio of the composite system will decrease, and the interfacial impedance will increase, thereby affecting the cycle performance; when the ultrasonic frequency is too high, the desired polymer can be achieved in a shorter time, but at this time the inorganic filler has not achieved a completely high dispersion effect. When subsequently mixed with the positive electrode slurry, the inorganic filler will agglomerate, affecting the ionic and electronic conductivity of the electrode and reducing the coulombic efficiency.

[0162] Compared with Example 1, in Examples 12 and 13, the second polymerization temperature is too low, the monomer polymerization is incomplete, there are more free monomers in the composite slurry, the thermal stability of the free monomers is poor, and thus affects the overall thermal safety performance of the battery; the second polymerization temperature is too high, the product after monomer polymerization is more rigid, which is not conducive to lithium ion transmission, the solid-solid interface contact impedance is greatly increased, and the first-cycle coulomb efficiency and long-cycle performance are affected.

[0163] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0164] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a pole piece by heterogeneous polymerization, characterized in that: The method comprises: Mixing the monomer and the initiator, performing the first polymerization, and obtaining a prepolymer precursor solution; The prepolymerized precursor solution is introduced into at least one side of the current collector and a second polymerization is performed to form an interface flexible layer on at least one side of the current collector.

2. The method according to claim 1, characterized in that Before the step of mixing the monomer and the initiator and performing the first polymerization to obtain the prepolymer precursor solution, the method further comprises: preparing an active material layer on at least one side of the current collector.

3. The method according to claim 1, characterized in that After the monomer and the initiator are mixed and the first polymerization is performed to obtain a prepolymer precursor solution, the prepolymer precursor solution is introduced into at least one side of the current collector and the second polymerization is performed to form an interfacial flexible layer on one side of the current collector. The method also includes: mixing the prepolymer precursor solution with an active substance.

4. The method according to claim 3, characterized in that The active material includes one of a positive electrode active material and a negative electrode active material; Preferably, the positive electrode active material includes at least one of a nickel-cobalt-manganese ternary material, a nickel-cobalt-aluminum ternary material, lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium vanadium phosphate and a lithium-rich manganese-based material; Preferably, the negative electrode active material includes at least one of graphite, graphene, soft carbon, hard carbon, elemental silicon, silicon-oxygen material, silicon-carbon material, silicon-nitrogen composite material, silicon-based alloy, elemental tin, tin oxide, tin-based alloy, lithium metal, lithium alloy, lithium titanium oxide, transition metal oxide and transition metal sulfide.

5. The method according to any one of claims 1 to 4, characterized in that The polymerization degree of the prepolymer precursor solution is 5%-60%; Preferably, the viscosity of the prepolymer precursor liquid is η, and η satisfies: 0<η≤1000 Pa·s.

6. The method according to any one of claims 1 to 4, characterized in that The step of mixing the monomer and the initiator and performing the first polymerization to obtain a prepolymer precursor solution comprises: After the monomer, lithium salt, inorganic filler, conductive agent, crosslinking agent, initiator and solvent are mixed, the first polymerization is carried out to obtain a prepolymer precursor solution.

7. The method according to claim 6, characterized in that Based on the total mass of the monomer, the initiator, the lithium salt, the inorganic filler, the conductive agent and the cross-linking agent, the mass proportion of the monomer is 0.5%-30%; Preferably, the monomers include at least one of acrylate monomers, olefin nitrile monomers, cycloolefin monomers, vinylidene ester monomers, amide monomers, alkyl sulfides, sulfate monomers, borate monomers, cyanamide monomers and quaternary ammonium salt monomers; Preferably, based on the total mass of the monomer, the initiator, the lithium salt, the inorganic filler, the conductive agent and the cross-linking agent, the mass ratio of the lithium salt is 0.5%-30%; Preferably, based on the total mass of the monomer, the initiator, the lithium salt, the inorganic filler, the conductive agent and the cross-linking agent, the mass proportion of the inorganic filler is 5%-50%; Preferably, the mass percentage of the initiator to the mass percentage of the monomer is 0.1%-3%.

8. The method according to claim 6, wherein the D50 particle size of the conductive agent is 5 nm-1000 nm, preferably 10 nm-500 nm; Preferably, the D50 particle size of the inorganic filler is 2nm-500nm, preferably 10nm-300nm; Preferably, the inorganic filler includes at least one of an inorganic active filler and an inorganic inert filler; Preferably, the inorganic active filler includes at least one of an oxide active filler, a sulfide active filler, a halide active filler, a nitride active filler, a boride active filler and a hydride active filler; Preferably, the inorganic inert filler includes at least one of an oxide inert filler, a nitride inert filler, a boride inert filler, a halide inert filler, a dielectric ceramic inert filler, a ferroelectric ceramic inert filler, a piezoelectric ceramic inert filler, a diatomaceous earth inert filler, a mullite inert filler, a montmorillonite inert filler and a kaolin inert filler.

9. The method according to any one of claims 1 to 4, characterized in that: The first polymerization method includes at least one of thermal polymerization, photopolymerization and ultrasonic polymerization; Preferably, the first polymerization method includes heating ultrasonic polymerization which is a combination of thermal polymerization and ultrasonic polymerization; Preferably, the temperature of the heated ultrasonic polymerization is 30°C-100°C, preferably 40°C-60°C; Preferably, the frequency of the heating ultrasonic polymerization is 0.5 MHz-5.0 MHz; Preferably, the heating ultrasonic polymerization time is 1h-12h.

10. The method according to any one of claims 1 to 4, characterized in that The temperature of the second polymerization is 40°C-120°C; Preferably, the second polymerization time is 10s-2min; Preferably, the introduction method includes at least one of coating, spraying and dipping; Preferably, the introducing method comprises coating, and the coating comprises gravure coating.

11. The method according to claim 10, characterized in that The parameters of the gravure coating meet one of the following conditions: The gravure coating speed is 0.5m / min-10m / min; The gravure coating tension is 30N-200N; The coating thickness of the gravure coating is 0.5 μm-3 μm.

12. The method according to any one of claims 1 to 4, characterized in that The method further comprises: A solid electrolyte layer is prepared on the interface flexible layer.

13. A pole piece prepared by heterogeneous polymerization, characterized in that: It comprises a pole piece prepared by the method described in any one of claims 1 to 12.

14. A diaphragm-free battery, characterized in that: The diaphragm-free battery comprises a pole piece prepared by the method described in any one of claims 1 to 12 or a pole piece described in claim 13.

15. A solid-state battery, characterized in that: The solid-state battery includes a pole piece prepared by the method of any one of claims 1 to 12 or a pole piece according to claim 13.

Citation Information

Patent Citations

  • Ionic liquid gel polymer electrolyte suitable for large-scale positive electrode in-situ coating as well as preparation method and application of ionic liquid gel polymer electrolyte

    CN114976228A

  • Solid-state battery and double-initiation in-situ preparation method thereof

    CN116914241A

  • Solid electrolyte, preparation method and application thereof

    CN117855598A

  • High-surface-load thick electrode and preparation method thereof

    CN118352468A